(untitled) (Texas Journal of Philology, Culture and History, 2024)
The article studies the issue of the expression of nationality and the interpretation of human relations in the stories of the famous Uzbek writer Isajon Sultan. Based on the analysis of the author’s stories such as “Men, оnam va O‘rta Yer dengizi” (“Me, My Mother and the Sea of Middle Earth”), “Megaintellekt” (“Mega-Intellect”), “Ota raqsi” (“Dance of the Father”) the writer’s ideological views and artistic skill are expressed.